Marshall cavendish cambridge primary maths Pupil's book 3 - Tan, Siew Lian; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
Mathematics. 3, Pupil's Book by Marshall Cavendish is designed to introduce Grade 3 students to key mathematical concepts. It covers topics such as addition, subtraction, multiplication, division, fractions, and basic geometry. The book uses clear explanations, engaging illustrations, and real-world examples to help students develop a solid understanding of math. Through practice exercises, problem-solving tasks, and interactive activities, the book encourages students to apply math concepts in various contexts, fostering both computational skills and critical thinking abilities at an early stage in their learning journey.